SEROPOSITIVITY FOR HEPATITIS B AND C IN VOLUNTARY BLOOD DONORS - Shah, Syed Mukhtar Ali; Khattak, Imran -uddin; Ali, Abid; Tariq, Muhammad (Journal of Ayub Medical College Abbottabad, 2010)
Background: After the introduction of blood banks and better storage techniques blood is more widely used in patients for various indications. In Pakistan more than 1.5 million pints of blood are collected each year. Hepatitis B and C virus infections are known to occur in the general population and due to their mode of transmission through blood and blood products, it has made safe blood transfusion difficult and screening of blood absolutely necessary. Objectives of this study were to estimate frequency of Hepatitis B and C in blood donors of local area and recommend measures for safe blood transfusion. Methods: This retrospective cross-sectional study was conduced at the Blood Bank, Department of Pathology, Khyber Teaching Hospital, Peshawar from 1st January 2007 to 31st December 2008. It was carried out on 32,042 voluntary, non-remunerated healthy blood donors. They were screened for Hepatitis B surface antigen (HBsAg) and anti-hepatitis C antibodies (antiHCV antibodies) by ELISA. The patients’ age ranged from 18-52 years. They were all males. Results: Out of 32,042 donors, 632 (1.97%) patients were positive for HBsAg, and 502 (1.57%) were positive for anti-HCV antibodies. Conclusion: Incidence of Hepatitis B and C is varying in different areas. It is recommended that properly screened blood only, using a reliable method like ELISA, be transfused to the patients. Keywords: HBsAg, HCV, ELISA, blood donors, blood transfusion